Wearable resistance acutely enhances club head speed in skilled female golfers. Issue 5 (October 2019) - Macadam, Paul; Chau, Anita; Cronin, John
Golf is a skill-based sport which requires optimal swing mechanics to improve golf performance. As practitioners seek training methods to improve swing kinetics without compromising swing kinematics, loading through wearable resistance is one training modality which enables the golf swing to be performed in an overloaded manner. The purpose of this research therefore was to explore the acute effects of wearable resistance on golf swing performance measures. A randomised cross-over design was used with five skilled female golfers (22.0 ± 2.5 years, 163.1 ± 3.3 cm, 57.1 ± 3.4 kg and handicap 4 ± 1.2) who performed a series of golf shots with and without wearable resistance of 1.6 kg (∼2.8% body mass) attached laterally to the posterior trail side of the body. Flightscope launch monitor and force plate technology were used to quantify changes in club head speed and ground reaction forces. Using a paired t-test used for statistical analysis, significant ( p < 0.05) acute increases were found in club head speed (3.5%, p = 0.03), relative vertical ground reaction forces (11.4%, lead side, p = 0.01) and relative mediolateral ground reaction forces (7.1%, trail side, p = 0.03) with wearable resistance as compared to the unloaded condition. Wearable resistance enables a player to perform golf shots in an overloaded manner resulting in significant improvements in club head speed. Future research is required to assess the long-term adaptations to this form of loading on golf swing performance.